KETIDAKSETARAAN GENDER SEBAGAI MEDIASI PENGARUH BUDAYA PATRIARKI TERHADAP PARTISIPASI PEREMPUAN PADA POSISI KEPEMIMPINAN DALAM BISNIS KELUARGA DI JAWA TIMUR - Fionna Benita (Ma Chung Press, 2021)
Family business supports the economy of countries in Asia, including Indonesia. However, many family businesses cannot continue their existence as family-owned businesses because of their top-level management's lack of leadership skills. The dominance of male involvement in business leadership indicates a patriarchal culture that can lead to gender inequality, where women are judged not based on their leadership qualities. Women have an excellent opportunity to improve company performance. This study aims to analyze the influence of patriarchal culture on gender inequality and gender inequality as a mediation of the influence of patriarchal culture on women's participation in leadership positions in family businesses in East Java. The research was conducted by surveying 102 female respondents who work in family businesses owned by their family members—data analysis using path analysis. The results of this study are (1) patriarchal culture has a significant positive effect on gender inequality. (2) the influence of patriarchal culture mediated by gender inequality is significantly negative on women's participation in leadership positions.